BETWEEN UTOPIA AND DYSTOPIA: MOSES FINLEY AND THE ATHENIAN DEMOCRACY VERSUS MOSES FINLEY AND THE ANCIENT ECONOMY. (December 2015) - NAFISSI, MOHAMMAD
Abstract : Modern scholarly accounts of ancient Greece and more particularly the research programme which broadly frames Moses Finley's contributions are generally traced to George Grote's politically anchored History of Greece and re‐evaluationof Athenian democracy. However, notwithstanding their far‐reachinginfluence, Finley's writings display an exceptional complexity that has invited a wide spectrum of contradictory interpretations and evaluations. This article extends my previous study of Finley's Athens by locating and exploring an unresolved and still significant debate that he held with himself through the major political and economic writings of his last period (1973–85). It thereby discloses the normative, theoretical, and empirical demands that, on the one hand, informed his account of 'the ancient economy' and necessitated its overall incoherence, and, on the other, allowed for a coherently normative account of 'ancient politics'. In the process, some notable claims about Finley's work and politics are clarified, and it is shown why 'Finley's ghost is [still] everywhere' even though the short twentieth century that spanned his life, posed its major questions and set the context and constraints of his answers, has long been over.